Aberrant expression of the pore-forming KATP channel subunit Kir6.2 in hippocampal reactive astrocytes in the 3xTg-AD mouse model and human Alzheimer's disease. (12th November 2016) - Griffith, Chelsea M.; Xie, Mi-Xin; Qiu, Wen-Ying; Sharp, Andrew A.; Ma, Chao; Pan, Aihua; Yan, Xiao-Xin; Patrylo, Peter R.
Graphical abstract: Highlights: Alzheimer's pathology is characterized by plaques, tangles and neuroinflammation. Aged 3xTg-AD mice recapitulate these AD characteristics. Aged 3xTg-AD mice and human AD tissue exhibit reactive astrocytes in hippocampal gray and white matter. 3xTg-AD hippocampi exhibit increased plasma membrane Kir6.2, but not Kir6.1. Increased Kir6.2 localizes to reactive astrocytes in 3xTg mice and human AD tissue. Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by beta-amyloid (Aβ) deposition, neurofibrillary tangles and cognitive decline. Recent pharmacologic studies have found that ATP-sensitive potassium (KATP ) channels may play a role in AD and could be a potential therapeutic target. Interestingly, these channels are found in both neurons and astrocytes. One of the hallmarks associated with AD is reactive gliosis and a change in astrocytic function has been identified in several neuropathological conditions including AD. Thus the goal of this study was to examine whether the pore-forming subunits of KATP channels, Kir6.1 and Kir6.2, are altered in the hippocampus in a cell type-specific manner of the 3xTg-AD mouse model of AD and in human AD tissue obtained from the Chinese brain bank. Specifically, in old 3xTg-AD mice, and age-matched controls, we examined glial fibrillary acidic protein (GFAP), glutamine synthetase (GS), Kir6.1 and Kir6.2 in hippocampal region CA1 with a combination of immunoblotting and immunohistochemistry (IHC). A time point was selected when memory impairment and histopathological changes have been reported to occur in 3xTg-AD mice. In human AD and age-matched control tissue IHC experiments were performed using GFAP and Kir6.2. In the hippocampus of 3xTg-AD mice, compared to wild-type controls, Western blots showed a significant increase in GFAP indicating astrogliosis. Further, there was an increase in Kir6.2, but not Kir6.1 in the plasma membrane fraction. IHC examination of hippocampal region CA1 in 3xTg-AD sections revealed an increase in Kir6.2 immunoreactivity (IR) in astrocytes as identified by GFAP and GS. In human AD tissue similar data were obtained. There was an increase in GFAP-IR in the stratum oriens (SO) and alveus (ALV) of CA1 concomitant with an increase in Kir6.2-IR in cells with an astrocytic-like morphology. Dual immunofluorescence revealed a dramatic increase in co-localization of Kir6.2-IR and GFAP-IR. Taken together, these data demonstrate that increased Kir6.2 is seen in reactive astrocytes in old 3xTg-AD mice and human AD tissue. These changes could dramatically alter astrocytic function and subsequently contribute to AD phenotype in either a compensatory or pathophysiological manner.